Neuroblastoma Current State and Recent Updates - Gowda, Chandrika (IntechOpen, 2017)
Neuroblastoma (NBL) is the most common extracranial solid tumor of childhood, with about 700 new cases of neuroblastoma seen each year in the United States. The 5-year survival rate for children with high-risk NBL is only 50-60%, and this survival rate has not improved over the last 10 years. High-risk patients receive multimodality treatment, including chemotherapy, surgery, radiation therapy, biologic therapy and immunotherapy, all of which are associated with significant morbidity. Recent years have seen many advances in treatment of neuroblastoma, including therapeutic MIBG, immunotherapy, and personalized targeted therapy based on the genetic alterations seen in the tumor. The primary objective of this book is to provide the readers with a comprehensive review of neuroblastoma, from clinical aspects and the currently available treatment to recent advancements and future directions in the field of NBL treatment. The topics and chapters have been compiled keeping in mind a diverse group of readers in different areas of specialty such as pediatric oncology, surgery, radiation oncology, and immunology, as well as physician scientists and basic researchers working in the field of neuroblastoma.